2017
DOI: 10.1021/acs.jctc.7b00073
|View full text |Cite
|
Sign up to set email alerts
|

Bridging Single- and Multireference Domains for Electron Correlation: Spin-Extended Coupled Electron Pair Approximation

Abstract: We propose a size-consistent generalization of the recently developed spin-extended configuration interaction with singles and doubles (ECISD), where a CI wave function is explicitly spin-projected. The size-consistent effect is effectively incorporated by treating quadruples within the formulation of coupled electron pair approximation. As in coupled-cluster theory, quadruple excitations are approximated by a disconnected product of double excitations. Despite its conceptual similarity to the standard single-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 116 publications
(278 reference statements)
1
32
0
Order By: Relevance
“…While there have been attempts to merge a symmetry-projected mean-field reference with a symmetry-adapted cluster operator [17,18], practical attempts to projectively restore the symmetries of a broken-symmetry coupled cluster wave function have only been made in the past few years. Duguet [19,20] and Scuseria [21] have proposed independent ways to achieve this, and Tsuchimochi and Ten-no have provided a third approach [22], albeit so far at the linearized coupled cluster level.…”
Section: Introductionmentioning
confidence: 99%
“…While there have been attempts to merge a symmetry-projected mean-field reference with a symmetry-adapted cluster operator [17,18], practical attempts to projectively restore the symmetries of a broken-symmetry coupled cluster wave function have only been made in the past few years. Duguet [19,20] and Scuseria [21] have proposed independent ways to achieve this, and Tsuchimochi and Ten-no have provided a third approach [22], albeit so far at the linearized coupled cluster level.…”
Section: Introductionmentioning
confidence: 99%
“…In Table I the uncorrected and corrected second-order energies, E 2 and L (Eqs. (24) and (30)). The level-shift correction is essential to keep the qualitative results of rSUPT2.…”
Section: B Multiple Bond Dissociation: H2o and N2mentioning
confidence: 94%
“…Therefore, the DIIS convergence is somewhat slow with the present implementation. Nevertheless, other preconditioning schemes are available to improve the convergence behavior, 24 and we will test and report their performances in a separate paper.…”
Section: Computational Detailsmentioning
confidence: 99%
“…The estimated gaps of ECISD and ECISD+Q are 7.9 and 22.8 kcal mol -1 , which are somewhat smaller than the SC-LCTSD and RASPT2 results. We have also performed a variety of spin-extended linearized CC calculations [10] to capture size-consistent effects, but found that their correlation energies diverge for this system because of intruder states; the ECISD first excited state lies relatively close to the ground state. While EACCSD is stable in this respect, and is deemed to be a better approximation than ECISD, it gave a potential curve that is quite similar to ECISD+Q, with a gap of 23.1 kcal mol -1 .…”
Section: Mn Dimermentioning
confidence: 99%
“…With this form, SUHF became a versatile tool for studying degenerate systems with the same computational scaling as HF. [6][7][8][9] Spin-projection on broken-symmetry CC, which we call spinextended CC (ECC), [10,11] is therefore an attractive candidate for describing both static and dynamical correlation effects (we have to clarify that it is different from the extended coupled-cluster of Arponen, which was derived from the bivariational principle in 1983 [12] ) and many authors have explored its potential. [11,13,14] However, challenges remain in combining CC and spin-projection, with two particular difficulties.…”
Section: Introductionmentioning
confidence: 99%